Antiviral potential of kelulut honey against SARS-CoV-2 - Ismail, Che Muhammad Khairul Hisyam; Ismail, Azlini; Abdul Hamid, Azzmer Azzar; Mohd Abdul Razak, Mohd Ridzuan; Mokhtar@Makhtar, Khairani Idah; Lestari, Widya; Mustafa Al-Ahmad, Basma Ezzat (Institute for Medical Research (IMR), National Institutes of Health, Ministry of Health (MOH), Malaysia, 2025)
INTRODUCTION: The ongoing spread of the SARS-CoV-2 Omicron variant continues to pose global health challenges, harbouring multiple sites of mutations. This variant exhibits enhanced immune evasion capabilities, raising concerns about the effectiveness of current vaccine strategies. Meanwhile, kelulut honey (KH) has emerged as a promising functional food, distinguished by its distinctive flavour and bioactive properties. OBJECTIVE(S): This study aimed to investigate the antiviral potential of KH against SARS-CoV-2. MATERIALS & METHODS: KH was obtained from Bukit Kuin 2, in Kuantan, Pahang, Malaysia (3°52’54.9”N 103°12’27.4”E). The antiviral potential of KH was assessed by investigating its ability to inhibit both the wild-type and Omicron SARSCoV-2-induced cytopathic effect (CPE) in Vero E6 cells (ATCC-CRL-1586). Nirmatrelvir was used as a reference drug. Experiments were done in biological and experimental replicates (n = 9). RESULTS: Both KH and nirmatrelvir caused dose-dependent inhibition of CPE-induced activity by both wild-type and Omicron SARS-CoV-2 variants. For the wild-type SARSCoV-2, 1H and 4H-pretreatment with KH at a non-cytotoxic concentration of 2.5% (v/v) inhibited CPE-induced activity by 56.7 ± 9.96 % (IC50 = 7.52% v/v) and 40.9 ± 11.6 % (IC50 = 9.3% v/v), respectively. Notably, KH at 2.5% (v/v) showed higher inhibition of CPE-induced activity against the Omicron variant, with 114.3 ± 7.84 % (IC50 = 2.36% v/v) and 92.7 ± 4.44 % (IC50 = 1.76% v/v) observed after 1H- and 4H-pretreatment, respectively. In comparison, nirmatrelvir at a concentration of 6.25 μM exhibited 111.89 ± 23.55 % (IC50 = 1.8 μM) and 121.6 ± 15.25 % (IC50 = 2.11 μM) inhibition of CPE-induced activity against wild-type SARS-CoV-2 for 1H- and 4H-pretreatment, respectively. For the Omicron variant, nirmatrelvir showed 140.3 ± 11.1% (IC50 = 2.14 μM) and 117.1 ± 7.05 % (IC50 = 2.24 μM) inhibition of CPE-induced activity at 6.25 μM for 1H- and 4H-pretreatment. CONCLUSION: KH exhibits antiviral activity against SARSCoV-2 wild-type and Omicron variants, as indicated by its ability to inhibit the induced cytopathic effect upon viral infection onto Vero E6 cells. These findings suggest that KH could serve as a complementary or alternative therapeutic against CoV-2 infections.